Buddhism and Non-Violent World: Examining a Buddhist Contribution to Promoting the Principle of Non-Violence and a Culture of Peace (In Factis Pax: Journal of Peace Education and Social Justice, 2014)
This paper examines a Buddhist contribution to promoting the principle of non-violence and culture of peace. The opposition to violence has been one of the cardinal principles of Buddhism, which is stated in the Dhamapada: “All tremble at violence; all fear death. Seeing others as being like yourself, do not kill or cause others to kill. All tremble at violence; life is dear for all. Seeing others as being like yourself, do not kill or cause others to kill.” Further, Buddhism since its beginning has developed the analysis of psychologically-oriented suffering including violence by means of eradication of its cause and achievement of internal serenity and this paper explores how the Buddhist analysis of human mind deepens the psychological dynamics of violence and unfolds internal dimension of peace for more humane world.